Chemical, spectroscopic characterization, molecular modeling and antibacterial activity assays of a silver (I) complex with succinic acid - Paris Junior, José Alberto; Rocchi, Ana Júlia Salvador; Biagioni, Bruno Torquato; Cavicchioli, Maurício; Machado, Rachel Temperani Amaral; Pavan, Fernando Rogério; Corbi, Pedro Paulo; Lustri, Wilton Rogério; Pereira, Douglas Henrique; Massabni, Antonio Carlos (Eclética Química, 2021)
A silver(I) complex with succinic acid in the form of succinate is presented. Chemical characterization confirms the molecular composition Ag2C4H4O4 for the complex. Infrared spectra suggest a bidentate coordination of both carboxylate groups of succinates to the two Ag(I) ions. Density functional theory (DFT) studies were used in the structures of succinic acid and Ag(I) succinate complex with coordination formula [Ag2(C4H4O4)] in order to optimize them to their minimum energy. The studies confirmed that each carboxylate group of the succinate anion is coordinated to one silver atom by the two oxygen in a bidentate mode and the bond lengths O···Ag theoretically determined range from 2.325 to 2.338 Å. The complex [Ag2(C4H4O4)] showed in vitro antibacterial activity against the bacterial strains of Staphylococcus aureus, Bacillus cereus, Escherichia coli and Pseudomonas aeruginosa complex. Anti-Mycobacterium tuberculosis analyses were also performed and the [Ag2(C4H4O4)] complex was shown to be active over M. tuberculosis H37Rv strain with MIC90 of 23.94 μg mL-1 while succinic acid itself showed a value higher than 25.00 μg mL-1.